A Comprehensive Review of Spatial Domain-Based Image Steganography Techniques - Bushra Abdullah Shtayt, Assist Prof. Dr. Nur Haryani Binti Zakaria, Dr. Nor Hazlyna Harun (International Journal of Advanced Science and Technology, 2020)
Over the past decades, digital technologies have grown rapidly, information circulation has become increasingly common across open and available Internet for all, making telecommunication security face major challenges. Digital steganography like text, image, video, or audio indicates the manner of hiding confidential messages with the aim of covert communication. Thus, this study intends to conduct a comprehensive review of work related to spatial domain-based image steganography techniques. In addition, this study will present a comprehensive review in taxonomical form along with a full description of the steganography of the image including the general scheme, applications and its fundamental requirements including various criteria for performance evaluations conducted in the area of stego-image from various aspects such as imperceptibility, capacity, and robustness.